Studies in pragmatism - Rescher, Nicholas (Rescher, Nicholas. Works. 2005 ;, 2005)
Set of studies of various ideas and theories that play a key role in traditional pragmatism and are important for the idealistic pragmatism Nicholas Rescher long was engaged in developing.